Struktur Kepemilikan, Kinerja Perusahaan, dan Dewan Independen sebagai Moderasi - Jurnali, Teddy; Meiliana, Meiliana; Septiany, Sheila; Jenny, Jenny (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p01, 2024)
This research aims to examine the influence of ownership structure consisting of ownership concentration, managerial ownership, institutional ownership and foreign ownership on company performance. The research objects include all companies that publish annual reports and are listed on the Indonesia Stock Exchange for the period 2018 to 2022. The purposive sampling method was used to determine the sample and obtained 1,926 data as objects of observation. Data analysis uses the panel regression analysis method. The research results show that ownership concentration and managerial ownership have a significant positive correlation with company performance, foreign ownership has a significant negative correlation with performance, institutional ownership is not significant with performance, and an independent board is unable to moderate ownership structure on company performance. Keywords: Ownership Structure; Board Independence; Firm Performance